STUDY ON THE INHIBITORY EFFECT OF ALLICIN ON HUMAN GASTRIC CANCER CELL LINE SGC-7901 AND ITS MECHANISM - Tao, Mei; Gao, Linghan; Pan, Jie; Wang, Xiaoye (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Allicin is the main active constituent of Allium sativum L., which is characterized by broad antibacterial spectrum (MarkosN et al., 2008; Chen et al., 2008); it also has apparent inhibitory effects on a variety of tumors. The Objective of the paper is to study the inhibitory effect of allicin on human gastric cancer cell line SGC-7901. Materials and Methods: MTT assay and flow cytometry technique were applied to determine the inhibition rate of allicin on human gastric cancer cell line SGC-7901. The results shows that different concentrations of allicin apparently inhibited the gastric cancer SGC7901 cells, cell growth inhibition rates in the experimental groups showed an upward trend with increased allicin concentration, which were concentration-dependent. Results: Flow cytometry results found that the cell cycle was arrested in the G2/M phase. Allicin has an apparent inhibitory effect on proliferation of gastric cancer cells, and can induce their apoptosis. Conclusion: Compared with other chemotherapeutic drugs, allicin’s anti-tumor effect is better; and toxic and side effects are relatively small.